(untitled) (Journal of Nepal Geological Society, 2013)
The Siwalik Group constitutes an important archive of Himalayan uplift and related climate changes. Compositional and textural properties of Siwalik sandstones are important parameters for the reconstruction of source lithology, uplift, and the unroofing history of the Himalaya. This study examines fluvial sandstones of the Siwalik Group along the Karnali River, where the large paleo-Kamali River is expected to have flow ed. Modal QFL analysis shows that the sandstones are mainly sub-litharenites or litharenites. Multivariate statistical analysis using Principal Component Analysis (PCA)and the Weltje method shows light variations in sediment composition occur between the Chisapani and Baka Formations. These variatio ns are mainly linked to the source area and tectonics rather than to facies, grain size, or climate. The detrital modes of the sandstones indicate recycled orogen provenance. Comparison of the detrital modes with previous studies indicates that the Higher Himalaya and Lesser Himalaya zones were a common source area throughout the time of deposition. However, subtle changes in feldspar and biotite contents indicate significant supply of detritus derived from the Higher Himalaya after 9.6 Ma.